Correlation of glycosylated hemoglobin level with the severity of coronary artery disease in diabetic patients - Hossam Eldin M Mahmoud; Abdel Rahman A Elsaied; Mohammed H Hassan (Journal of Biology and Medicine - Peertechz Publications, 2020)
Background: Diabetes Mellitus (DM) is known to cause microvascular and possibly macrovascular complications as it one of the major risk factors for Coronary Artery Disease (CAD). CAD is a major cause of death in developed countries. The study aims to assess the relation of glycated Hemoglobin (HbA1c) levels and severity of CAD in diabetic patients. Patients and methods: The study included 200 patients with type II diabetes mellitus and symptoms suggesting CAD in whom coronary angiography was indicated in internal medicine department, Qena University hospitals. Full medical history was taken with special concern on presence of associated co-morbidities (Hypertension, dyslipidemias, smoking history). They were assessed according to HBA1C level and Gensini score. Electroencephalogram and transthoracic echocardiography were performed to the included patients. Patients were divided into 6 groups according to HBA1C starting from 4 to >14 and 7 groups according to Gensini score from 0 to 140, 3 groups according EF% (Ejection fraction) from <40% to >50%. Results: Our study included 132 females with mean age 52.33±9.618 and 68 males with mean age 55.04±10.147, One hundred and eleven patients were hypertensive, 68 patients were smoker, dyslipidemia found in 116 patients, 84 patients had ECG ischemic changes and RSWMA (Segmental wall motion abnormality at rest) by transthoracic echocardiography found in 88 patients. A statistically significant positive correlations between HBA1C with Gensini score, smoking, dyslipidemia, hypertension were present (p<0.05). Conclusion: HbA1c can be used as a predictor of severity of coronary artery disease measured by Gensini score as patients with a higher level of HbA1c had significant severe lesions with higher Gensini scores.